Influence of Public Policy on Business Strategy: A Systematic Literature Review and Thematic Visualization Analysis - Ahyar Junaedi; Mohamad Rafii; Irwani (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2024)
Purpose — The primary purpose of this study is to investigate how political decisions and public policies shape the formulation and implementation of business strategies across various organizational contexts.Method — Following the PRISMA guidelines, this study commenced with an extensive search in the Scopus database, initially identifying 281 articles. However, after rigorous relevance and quality screenings, only six articles were selected. VOSviewer was then employed for advanced visual analytics to explore the interconnections and thematic developments within the academic discourse, providing deeper insights into the literature's structure and evolution.Result — The findings reveal a complex interplay between business strategies and public policies, where alignment with governmental directives is associated with increased innovation and market adaptability. Conversely, misalignments tend to result in higher compliance costs and reduced strategic agility. The visualizations highlight key areas such as sustainability, regulatory frameworks, and strategic management, underscoring their crucial roles in shaping how businesses respond to policy changes.Novelty — This Systematic Literature Review (SLR) combines thematic visualizations with systematic data analysis to provide a clearer understanding of the dynamic relationship between policy decisions and business strategies. This approach not only reveals the current state of research but also traces the evolution of key themes over time, offering insights into the shifting focuses of both academic and practical perspectives.